2020
DOI: 10.1186/s12958-020-00634-8
|View full text |Cite
|
Sign up to set email alerts
|

Androgen levels in the fetal cord blood of children born to women with polycystic ovary syndrome: a meta-analysis

Abstract: Introduction Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders in reproductive-aged women. It is reported that intrauterine exposure to hyperandrogenism may induce the development of PCOS and associated complications in later life. To analyze the intrauterine androgen levels in infants born to PCOS mothers, we evaluated the androgen levels in fetal cord blood through a meta-analysis of observational studies. Material and methods The followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
6
1
Order By: Relevance
“…Although numerous animal studies laid the foundations of this developmental hypothesis for PCOS etiology [18,19], however, this theory was doubted in human for many years, and insufficient observational human studies were conducted with controversial results. The latest meta-analysis concluded that fetal cord blood testosterone and dehydroepiandrosterone (DHEA) levels were not related to PCOS, while the androstenedione (ADION) levels were tended to be reduced in newborns of PCOS mothers [20], which was opposite to the present hypothesis. It could be explained that maternal testosterone might be bound by sex hormone-binding globulin (SHBG) and then quickly degraded and converted by the placenta's high levels of aromatase into estradiol.…”
contrasting
confidence: 89%
“…Although numerous animal studies laid the foundations of this developmental hypothesis for PCOS etiology [18,19], however, this theory was doubted in human for many years, and insufficient observational human studies were conducted with controversial results. The latest meta-analysis concluded that fetal cord blood testosterone and dehydroepiandrosterone (DHEA) levels were not related to PCOS, while the androstenedione (ADION) levels were tended to be reduced in newborns of PCOS mothers [20], which was opposite to the present hypothesis. It could be explained that maternal testosterone might be bound by sex hormone-binding globulin (SHBG) and then quickly degraded and converted by the placenta's high levels of aromatase into estradiol.…”
contrasting
confidence: 89%
“…The authors suggest that T may be quickly degraded and converted by placental aromatase into E2 when passing through the placenta. However, cord blood A4 levels in female newborns were significantly lower in PCOS than in the control group ( 125 ). As explained in section 2, cord blood androgens are derived from both fetal adrenal as well as placental steroidogenesis.…”
Section: Hormonal and Metabolic Interactions In Pregnant Women With H...mentioning
confidence: 72%
“…Levels of DHEA and DHEAS in fetal cord blood were generally not associated with PCOS ( 73 , 74 , 88 , 95 ), but studies regarding T and A4 have produced conflicting results. A recent meta-analysis of seven studies (n= 570) found no significant differences in cord blood T levels between women with and without PCOS, irrespective of neonatal sex ( 125 ). The authors suggest that T may be quickly degraded and converted by placental aromatase into E2 when passing through the placenta.…”
Section: Hormonal and Metabolic Interactions In Pregnant Women With H...mentioning
confidence: 99%
See 1 more Smart Citation
“…The maternal conditions are demonstrated to be closely related to the endocrine function of sows and piglets [5]. Pregnant sows are characterized by a high level of oxidative stress, which further influences the endocrine function of the fetoplacental unit [6,7].…”
Section: Introductionmentioning
confidence: 99%